One‐Pot Synthesis of MgAlO Support for PtSn Catalysts over Propane Dehydrogenation. Issue 7 (17th February 2022) - Wang, Xiaohan; Hu, Huimin; Zhang, Ning; Song, Jiaxin; Fan, Xiaoqiang; Zhao, Zhen; Kong, Lian; Xiao, Xia; Xie, Zean
Abstract: The Mg−Al composite supports (MgAlO) with different Mg/Al ratios were prepared by hydrothermal method. Then a series of PtSn/MgAlO catalysts were prepared and the influence of Mg/Al ratios on the physicochemical properties and the catalytic performances for propane dehydrogenation were investigated. The catalysts were characterized by means of X‐ray diffraction, N2 adsorption‐desorption, H2 temperature‐programmed reduction, NH3 temperature‐programmed desorption and Raman. Compared with Al2 O3 and MgO support, MgAlO support is beneficial to the dispersion of Pt. And the dispersion of Pt is influenced by the Mg/Al ratios. When the ratio of Mg/Al is 1/10, the dispersion of Pt is the highest, which results in high propane dehydrogenation activity. Abstract : The Mg−Al composite supports (MgAlO) with different Mg/Al ratios were prepared by one‐pot hydrothermal method. The ratios of Mg/Al affected the structures and phy‐chemical properties of supports, which influenced the dispersions of Pt on PtSn/MgAlO catalysts and resulted in different catalytic performances.